Applied tensional analysis: Engaging practitioners and the constitutive shift. Issue 4 (September 2019) - Mease, Jennifer J
This article introduces applied tensional analysis as a methodological framework that integrates constitutive ontologies (that depict organizations as processes in constant states of emerging or becoming) with the applied need for practitioners to understand and navigate the everyday exigencies of their organizational experiences. Applied tensional analysis centers analysis on tensions as the key to understanding organizational becoming in contrast to approaches that assume organizations are stable entities and consequently focus on patterns, themes, or laws. The applied tensional analysis framework offers four analytical foci (context, tensions, enacted responses, and repertoires) organized into two loops (analytical and change) as guides for data collection and analysis. While the analytical loop orients scholars to the current and past configurations of an organization's emergence, the change loop emphasizes the multitude of available responses to a particular tension and the constitutive implications of those responses for organizational becoming. As a new methodological approach, applied tensional analysis suggests that organizational knowledge requires more than awareness of what an organization is and includes awareness of organizational potential and what an organization might become .